Dielectric Property of Waste Tire Dust-Polypropylene (WTD-PP) Composite For High Voltage Outdoor Insulation Application - Aman, Aminudin; Abdullah, Abdul Rahim (2012)
High voltage insulation technology is still undergoing continuous development and improvement from time to time, from conventional ceramic type since to newly polymeric composite insulation material. This includes the development of new composite materials. This paper focused on the possibility of using Waste Tire Dust-Polypropelene (WTD-PP) composite with Alumina Trihydrate (ATH) as the main reinforcement filler for high voltage insulation material. Compound of WTD-PP without and with ATH were prepared with different compositions of WTD-PP content and different amount of ATH filler. A step of processes to produce this newly polymeric composite is presented in this paper. The basic requirement to determine and evaluate the performance of the selected materials as high voltage outdoor application shall comply to the international standard, BS EN 62039:2007. This standard lists several requirements of electrical and mechanical properties that must be fulfilled for materials to be used for high voltage outdoor application. Experimental work has been conducted on the dielectric strength of WTD-PP composite. Breakdown test complying with BS EN 60243-1:1998 is adopted to examine the breakdown strength of this newly polymeric composite. It was found that the breakdown strength of these composites is less than 10kV/mm due to it carbon black content but can be used for lower voltage insulation application.